Mental Health and Mental Illness in Later Life - Smyer, Michael A.; Bartels, Stephen J. (Generations)
A special issue on mental health and mental illness in later life. Topics discussed include the latest developments in basic research in, effective assessment and treatment of, and public policy on aging and mental health.